Agroforestry systems: Meta‐analysis of soil carbon stocks, sequestration processes, and future potentials. (4th September 2018) - Shi, Lingling; Feng, Wenting; Xu, Jianchu; Kuzyakov, Yakov
Abstract: Agroforestry (AF) has the potential to restore degraded lands, provide a broader range of ecosystem goods and services such as carbon (C) sequestration and high biodiversity, and increase soil fertility and ecosystem stability through additional C input from trees, erosion prevention, and microclimate improvement. Advantages and processes for global C sequestration in AF are unknown. We used a meta‐analysis of 427 soil C stock data pairs grouped into four main AF systems—alley cropping, windbreaks, silvopastures, and homegardens—and evaluated changes in AF and adjacent control cropland or pasture. Mean soil C stocks in AF (1‐m depth) were 126 Mg C·ha −1, which is 19% more than that in cropland or pasture. The highest C stocks in soil were in subtropical homegardens, AF with younger trees, and topsoil (0–20 cm). Increased soil C stocks in AF were lower than aboveground C stocks in most AF systems, except alley cropping. Homegardens stored the highest C in both aboveground and belowground, especially in the subsoil (20–100 cm). Advantages of AF ecosystem services focusing on mechanisms of belowground C sequestration were analyzed. AF could store 5.3 × 10 9 Mg additional C in soil on 944 Mha globally, with most in the tropics and subtropics. AF systems could greatly contribute to global soil C sequestration if used in larger areas. Future investigations of AF should include (a) mechanistic‐ and process‐based studies (instead of common monitoring and inventories), (b) models linking forest and crop growth with soil water and C and nutrient cycling, and (c) accurate assessments of the AF area worldwide based on the remote sensing approaches.